Analysing virtual organisation risk sources: an analytical network process approach. (1st January 2012) - Alawamleh, Mohammad; Popplewell, Keith
SMEs have to collaborate with other enterprises in a virtual organisation (VO) forms to cope with an increasingly dynamic and competitive environment. Despite the increased interest in the area of collaboration information is still lacking about the risk sources of VO. This paper aims to reinforce the proposal for an integrated methodology to classify, manage and assess network level risk sources in VO and discusses the advantages of AHP/ANP over the other multi-criteria decision making (MCDM) methods before discussing the analytical hierarchy process (AHP) and the analytical network process (ANP) methods and the advantages of ANP over the AHP. This will be followed by illustrations of how ANP can be used to assess VO risk sources as part of the framework to support the final decision of VO collaboration. ANP will be used to set up a panel of weights of risk sources to define which risks are more serious. Overall, insights from the research and the process suggested in this research will aid SMEs in making a less risky decision.